2013
DOI: 10.1111/jch.12199
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure in Overweight and Obese Youth: Implications for Screening

Abstract: In the absence of evidence-based guidelines for high blood pressure screening in asymptomatic youth, a reasonable strategy is to screen those who are at high risk. The present study aimed to identify optimal body mass index (BMI) thresholds as a marker for high-risk youth to predict hypertension prevalence. In a cross-sectional study, youth aged 6 to 17 years (n=237,248) enrolled in an integrated prepaid health plan in 2007 to 2009 were classified according to their BMI and hypertension status. In moderately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 37 publications
2
42
1
10
Order By: Relevance
“…However, the impact of higher BMI was greatest among the higher blood pressure groups, suggesting excess body weight may be particularly problematic for individuals already on a trajectory toward developing higher blood pressure. Our results support recommendations for blood pressure screening of children and adolescents who are overweight and obese 32 and population-based strategies that focus on maintaining a healthy weight. Similar to previous longitudinal studies 19 , we found that cigarette smoking was a significant risk factor and associated with an upward shift in trajectories for those in the high-normal and prehypertensive groups (approximately 75% of population).…”
Section: Discussionsupporting
confidence: 73%
“…However, the impact of higher BMI was greatest among the higher blood pressure groups, suggesting excess body weight may be particularly problematic for individuals already on a trajectory toward developing higher blood pressure. Our results support recommendations for blood pressure screening of children and adolescents who are overweight and obese 32 and population-based strategies that focus on maintaining a healthy weight. Similar to previous longitudinal studies 19 , we found that cigarette smoking was a significant risk factor and associated with an upward shift in trajectories for those in the high-normal and prehypertensive groups (approximately 75% of population).…”
Section: Discussionsupporting
confidence: 73%
“…Subjects at validation sites were more likely to be obese, and more likely to have stage 2 systolic BP elevation at their incident elevated BP measurement, than subjects at the derivation site. Presence of obesity and stage 2 systolic BP elevation would likely confer higher risk of subsequent hypertension, 32, 33 and the risk of hypertension was demonstrably higher at validation sites compared to the derivation site. Although these baseline covariates (systolic BP percentile, prior BP, and BMI percentile) were included in our regression model predicting hypertension risk, case mix differences across sites could nonetheless have contributed to poor external validation, 29 because the relative weights of various covariates were based upon a population at lower risk of eventually developing hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…This sharp progression of probability is also evident in kids and adolescents [810], though a significant decline might be observed in the past 10 years [11]. …”
Section: Obesity As a Comorbidity In Arterial Hypertensionmentioning
confidence: 98%